African catfish, clarias gariepinus as bio-indicator of water pollution in Aganan, River, Alimodian, Iloilo. - Albrecht, Katherine (Iloilo City UPHSI, 2000)
The deterioration of water quality has become increasingly evident, with the establishment of slaughterhouses, markets, piggeries, and poultry farms accompanied by a surge in population (Mendoza, 1989). Pollution in freshwater systems threatens the survival and growth of many aquatic organisms especially the fishes (Canoy, 1997). The use of the African catfish (Clarias gariepinus) as the test specimen lies on the fish's significance to Philippine fisheries. The catfish industry has garnered the attention of aquatic researchers for it is suitable for farming owing largely to its affordability and easy breeding. African catfish, Clarias gariepinus, were raised on 9 containers, 3 replicates on each site. Substrate and water were taken from each site. Physico-chemical parameters such as water temperature, pH, and DO of the sampling sites were measured every other day. The tissues were processed using the paraffin technique and studied under the light microscope. Kidney tissues taken from three replicates of 3 sites were found to have occluded tubular lumen. Liver tissues taken from 3 replicates of 3 sites showed swelling of sinusoids infiltrated with blood cells. Gill tissues from 3 replicates of 3 sites showed pervasive aberrations, which has the presence of clavate lamellae. Aberrations showed that water from Aganan River is polluted.
Research II : Research Manuscripts
Keywords: African catfish